Adverse drug reactions in therapeutic hypothermia after cardiac arrest. (March 2017) - Witcher, Robert; Dzierba, Amy L.; Kim, Catherine; Smithburger, Pamela L.; Kane-Gill, Sandra L.
Background: Therapeutic hypothermia (TH) improves survival and neurologic function in comatose survivors of cardiac arrest. Many medications used to support TH have altered pharmacokinetics and pharmacodynamics during this treatment. It is unknown if or at what frequency the medications used during TH cause adverse drug reactions (ADRs). Methods: A retrospective chart review was conducted for patients admitted to an intensive care unit (ICU) after cardiac arrest and treated with TH from January 2009 to June 2012 at two urban, university-affiliated, tertiary-care medical centres. Medications commonly used during TH were screened for association with significant ADRs (grade 3 or greater per Common Terminology Criteria for Adverse Events) using three published ADR detection instruments. Results: A total of 229 patients were included, the majority being males with median age of 62 presenting with an out-of-hospital cardiac arrest in pulseless electrical activity or asystole. The most common comorbidities were hypertension, coronary artery disease, and diabetes mellitus. There were 670 possible ADRs and 69 probable ADRs identified. Of the 670 possible ADRs, propofol, fentanyl, and acetaminophen were the most common drugs associated with ADRs. Whereas fentanyl, insulin, and propofol were the most common drugs associated with a probable ADR. Patients were managed with TH for a median of 22 hours, with 38% of patients surviving to hospital discharge. Conclusions: Patients undergoing TH after cardiac arrest frequently experience possible adverse reactions associated with medications and the corresponding laboratory abnormalities are significant. There is a need for judicious use and close monitoring of drugs in the setting of TH until recommendations for dose adjustments are available to help prevent ADRs.